Is the earnings-schooling relationship linear? A semiparametic analysis - Dacuycuy, Lawrence B. (Animo Repository, 2005)
Using data from Labor Force Surveys (LFS), this study implements additive models to analyze the impact of schooling on wages. It also uses the Sperlich, Tjostheim and Yang (2002) test to validate the existence of interaction terms. Results confirm that the earnings-schooling relationship exhibits convexity. However, the degree to which the said relationship is convex is materially affected by the presence of the interaction component in the additive wage function.